UNESCO-UNEVOC catalyses Networking and Partnership in TVET in the post-2015 agenda - Majumdar, Shyamal [Verfasser] (My University, 2014)
"UNESCO-UNEVOC International Centre (UNESCO-UNEVOC) is UNESCO's specialised centre for Technical and Vocational Education and Training (TVET) and acts as the hub of the UNEVOC Network. This article argues that future challenges in TVET like 'greening TVET' or 'youth unemployment' call upon robust partnership building and cooperation that supports development of TVET policies and strategies, knowledge sharing and capacity building." (Autorenreferat, BIBB-Doku)
Keywords: I 1.5 Internationale Organisationen & Institutionen; UNESCO; UNEVOC; Berufsbildung; Internationale Zusammenarbeit; Netzwerk